A method for preparing and applying two-dimensional porous oxide nanosheets with compressive strain

The preparation of nickel- and ytterbium-doped two-dimensional porous oxide nanosheets by Joule heat treatment and ball milling technology solves the problems of low preparation efficiency and high energy consumption in existing technologies, achieves high-efficiency HER performance improvement, and promotes the application of two-dimensional metal oxides in the field of electrocatalysis.

CN120535001BActive Publication Date: 2025-11-14SHANDONG HAIHUA GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511038319.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-11-14
Estimated Expiration
2045-07-28

AI Technical Summary

Technical Problem

Existing technologies struggle to efficiently prepare inexpensive and efficient two-dimensional metal oxide electrocatalysts, especially CeO2-based catalysts, which have limited HER performance in alkaline water splitting. Furthermore, traditional methods are time-consuming and energy-intensive, and it is difficult to uniformly introduce compressive strain within the catalyst.

Method used

Two-dimensional porous oxide nanosheets doped with nickel and ytterbium were prepared by using Joule heat treatment combined with ball milling and ultrasonic cleaning. Compressive strain was introduced into the catalyst through rapid heating and cooling and ball milling, resulting in large pore size and high specific surface area, thus optimizing the active sites.

Benefits of technology

This study achieved efficient and low-cost preparation of two-dimensional porous oxide nanosheets with compressive strain, significantly improving HER performance and even surpassing the performance of commercial Pt/C catalysts, demonstrating broad prospects for industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535001B_ABST
    Figure CN120535001B_ABST
Patent Text Reader

Abstract

This invention provides a method for preparing and applying two-dimensional porous oxide nanosheets with compressive strain, belonging to the field of electrochemical technology. The invention involves grinding and mixing mannose, lysine, and a metal salt, followed by Joule heat treatment of the mixture to induce a non-enzymatic browning reaction, thereby preparing compressively strained porous oxide nanosheets. These materials possess abundant porous structures, and the co-doping of rare earth elements and transition metals induces lattice compressive strain in CeO2 and generates abundant oxygen vacancies. The synergistic effect of lattice compressive strain and increased oxygen vacancy concentration effectively improves the stability of the catalyst and the activity of HER (hydrochemical reaction).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology and relates to a method for preparing and applying two-dimensional porous oxide nanosheets with compressive strain. Background Technology

[0002] The water electrolysis reaction comprises two half-reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The HER reaction currently primarily utilizes Pt-based noble metal catalysts, while the OER reaction mainly employs noble metal oxide catalysts such as IrO2 and RuO2. However, the limited reserves and high prices of noble metal catalysts restrict their large-scale application in water electrolysis. Therefore, the preparation of inexpensive and efficient water electrolysis catalysts is an urgent problem to be solved.

[0003] The unique structure and electronic properties of two-dimensional metal oxides (2D metal oxides) make them promising candidates for catalytic hydrogen production via water electrolysis. Compared to other metal oxides, 2D metal oxides exhibit higher electron mobility and carrier concentration, promoting electron transfer during electrocatalysis. Furthermore, 2D metal oxides possess more incongruent sites and a larger specific surface area, enhancing the interaction between reactants and catalysts. Their lower atomic coordination numbers at the edges also contribute to improved catalytic performance. In recent years, numerous methods have been developed for preparing 2D metal oxides, including mechanical exfoliation, liquid-phase methods, vapor deposition, and primary oxidation on metal sources (such as liquid metals, polished metals, and 2D metals). However, these methods typically require complex processes, are time-consuming and energy-intensive, and may even lead to metal contamination. Therefore, developing a new and efficient method for preparing 2D metal oxides is of great significance.

[0004] Although two-dimensional metal oxides have shown great promise in electrocatalytic hydrogen production, their inherent limitations restrict their development. For example, fluorite-type cerium dioxide (CeO2), as a stable oxide with multiple valence states and rich oxygen vacancies, is a promising HER electrocatalyst. However, the oxygen sites on CeO2 are unfavorable for hydrogen adsorption, limiting its HER performance. Therefore, developing CeO2-based catalysts with optimized hydrogen binding energies is crucial for HER in alkaline water splitting. Studies have shown that introducing compressive strain within the catalyst material is an effective strategy for regulating the binding strength of key reaction intermediates and enhancing catalytic activity. Compressive strain optimizes the adsorption strength of active sites for hydrogen by shortening the surface atomic distance and regulating the d-band center, and introduces and stabilizes vacancies within the catalyst, significantly enhancing catalytic performance. However, current methods mainly introduce compressive strain within the catalyst through interface engineering, resulting in compressive strain primarily distributed on the interfacial structure rather than uniformly distributed within the catalyst. Therefore, there is an urgent need to develop a simple and efficient method to introduce compressive strain within the HER catalyst without constructing interfaces.

[0005] Chinese patent document CN117448793A discloses a thin-layer two-dimensional oxide material and its preparation and application. This invention achieves the growth of a thin-layer two-dimensional oxide material by first treating the substrate with gas plasma, and then depositing oxides onto the plasma-treated substrate using chemical vapor deposition. While this invention can prepare thin-layer two-dimensional oxide nanosheets, the vapor deposition method requires high temperature and vacuum conditions, has low deposition efficiency, and uses complex and costly equipment.

[0006] Chinese patent document CN116288495A discloses a method for preparing Ru-based oxide catalysts with surface metal atom doping via ion exchange and its application. This invention introduces metal atoms and oxygen vacancies onto the surface of Ru-based oxides through ion exchange, resulting in a certain degree of compressive strain on the composite catalyst surface. This shortens the distance between Ru-O bonds, enhances the bond energy of Ru-O bonds, and improves the stability of the Ru-based oxide catalyst. While this patent achieves the adjustment of the compressive strain of the oxide lattice, the preparation process is cumbersome, requiring hydrothermal reaction and high-temperature calcination, which is time-consuming. Furthermore, the prepared oxides are particulate and do not involve the control of two-dimensional porous oxide nanosheets.

[0007] Chinese patent document CN116966911A discloses a trivalent rare-earth-doped cerium dioxide supported metal catalyst, its preparation method, and its application. This invention sequentially dops cerium dioxide with rare-earth element La and transition metal Ni via hydrothermal and deposition-precipitation methods, respectively, to improve the catalytic activity and stability of cerium dioxide. The method used in this invention requires 24 hours of hydrothermal reaction and 4 hours of conventional high-temperature calcination, making the process complex and time-consuming, and it does not involve the control of two-dimensional porous oxide nanosheets. Summary of the Invention

[0008] The purpose of this invention is to provide a method for preparing two-dimensional porous oxide nanosheets with compressive strain, which can solve the problems of low activity, poor stability, long reaction time, and high energy consumption of electrocatalysts prepared by traditional methods.

[0009] To solve the above-mentioned technical problems, the technical solution of the present invention is:

[0010] A method for preparing two-dimensional porous oxide nanosheets with compressive strain includes the following steps:

[0011] (1) After mixing mannose, lysine, nickel salt, cerium nitrate and ytterbium nitrate, solid-phase grinding was performed to obtain the first precursor;

[0012] (2) The first precursor is subjected to Joule heat treatment in air atmosphere to obtain the second precursor;

[0013] (3) The second precursor is added to a mixed solvent consisting of a protic solvent and a non-protic polar organic solvent, and after ultrasonic cleaning and vacuum drying, two-dimensional porous oxide nanosheets with compressive strain are obtained.

[0014] Further, in step (1), the nickel salt is nickel nitrate, nickel sulfate, or nickel acetate; the solid-phase grinding conditions are: ball weight percentage 10-20:1, ball mill speed 800-1500 r / min, and ball milling time 0.8-1.5 h.

[0015] Further, in step (1), the molar ratio of mannose, lysine, nickel salt, cerium nitrate, and ytterbium nitrate is 1:1.5-2.0:0.05-0.08:0.25-0.50:0.05-0.08.

[0016] Furthermore, in step (2), the conditions for Joule heat treatment are: heat treatment temperature 500-1600℃, heating rate 1500-3000℃ / s, and 3-5 Joule heat treatments.

[0017] Further, in step (3), the protic solvent is water or ethanol; the aprotic polar organic solvent is acetonitrile or acetone; and the volume ratio of the protic solvent to the aprotic polar organic solvent in the mixed solvent is 1:2-4.

[0018] Furthermore, in step (3), the ratio of the amount of the second precursor to the mixed solvent composed of the proton solvent and the non-proton polar organic solvent is 1g:9-15mL.

[0019] Furthermore, in step (3), the ultrasonic cleaning conditions are: ultrasonic cleaning time 0.3-0.5h, ultrasonic cleaning 2-3 times.

[0020] Furthermore, in step (3), the vacuum drying conditions are: drying time 5-10h, drying temperature 60-100℃.

[0021] Another object of the present invention is to provide an application of the two-dimensional porous oxide nanosheets with compressive strain prepared by the above method, using them as an electrochemical catalyst in the hydrogen evolution reaction (HER) under alkaline electrolyte.

[0022] In this invention, Joule heat treatment involves heating from room temperature to the target temperature and then naturally cooling back to room temperature, which is considered one cycle.

[0023] In this invention, ultrasonic cleaning refers to the process of dispersing the second precursor in a mixed solution, ultrasonically cleaning it for a certain period of time, and then filtering or centrifuging the resulting solid particles, which is represented as one cycle.

[0024] Compared with the prior art, the beneficial effects of this invention are as follows:

[0025] (1) The present invention uses Joule heat treatment technology to uniformly mix mannose, lysine and metal salt, and then calcine them under extreme conditions of rapid heating and cooling to obtain two-dimensional porous oxide nanosheets with compressive strain. This method has low raw material price, simple operation, high preparation efficiency and low energy consumption, and can be mass-produced.

[0026] (2) The ball milling process used in this invention has a dual function. First, it can grind the particles of the mixture into smaller sizes and mix the reactants more evenly, which is conducive to uniform heating and thus facilitates the in-situ synthesis reaction of the mixture by Joule heat treatment technology to obtain two-dimensional porous oxide nanosheets with compressive strain uniformly doped with nickel and ytterbium. Second, the rapid grinding and long grinding time can generate heat, which can pre-react the mixture, which is conducive to reducing the reaction conditions of Joule heat treatment technology and reducing the cost of the synthesis process.

[0027] (3) This invention, by co-doping CeO2 with nickel and ytterbium, can induce lattice compressive strain in the material, increase the density of oxygen vacancy sites, enhance the dissociation of water molecules at oxygen vacancy sites, and improve hydrogen adsorption at sites adjacent to oxygen vacancy sites. Simultaneously, the Yb-O chemical bond in Yb doping is stronger than the Ce-O chemical bond; therefore, Yb doping can stabilize oxygen vacancy sites and improve the stability of the catalyst. Thus, the two-dimensional porous oxide nanosheets rich in nickel and ytterbium possess catalytic properties.

[0028] (4) The two-dimensional porous oxide nanosheets with compressive strain of the present invention are constructed by a non-enzymatic browning reaction involving vigorous redox reactions between mannose and lysine. When lysine comes into contact with mannose at high temperature, the mixture reacts immediately to generate a large amount of gas, which can blow the molten mannose to form a layered structure. At the same time, it can induce the formation of a richer pore structure on the material surface, resulting in a larger specific surface area and exposing more active sites, thereby improving the activity of the catalyst. It has a synergistic effect with dual doping of Yb and Ni, and together they exhibit excellent basic HER performance.

[0029] (5) By changing the ratio of protic solvent to non-protic polar organic solvent, the ultrasonic cleaning time and the number of ultrasonic cleaning cycles, the present invention can not only remove impurities, organic residues and unreacted substances, but also optimize the specific surface area of ​​the material, thereby improving the catalytic performance of the catalyst in alkaline electrolyte for HER.

[0030] (6) The two-dimensional porous oxide nanosheets with compressive strain prepared in this invention exhibit outstanding performance in the hydrogen evolution reaction under alkaline electrolyte conditions. The material has a mesoporous and macroporous structure with a pore size range of 16-80 nm and a specific surface area range of 72.8-77.2 m•g. -2At 10 mA cm -2 At current densities of [specific values], the overpotential reached 28-42 mV, exceeding even the performance of commercial Pt / C electrocatalysts under the same conditions (45 mV @ 10 mA cm⁻¹). -2 ), with broad prospects for industrialization. Attached Figure Description

[0031] Figure 1 X-ray diffraction (XRD) patterns of two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3;

[0032] Figure 2 The image shows a partial magnified view of the X-ray diffraction patterns of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3.

[0033] Figure 3 Scanning electron microscope (SEM) image of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1;

[0034] Figure 4 Nitrogen adsorption-desorption (N2-BET) curves of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1;

[0035] Figure 5 Electron paramagnetic resonance (EPR) spectra of two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3;

[0036] Figure 6 Linear scanning voltammetry (LSV) performance test results of the two-dimensional porous oxide nanosheet catalyst with compressive strain prepared in Example 1 for the hydrogen evolution reaction;

[0037] Figure 7 Two-dimensional porous oxide nanosheets with compressive strain prepared for Examples 1 and Comparative Examples 1-3 were subjected to compressive strain at 10, 50, and 100 mA cm⁻¹. -2 The overpotential diagram below;

[0038] in, Figure 1 In this context, Intensity represents intensity, and 2θ represents the diffraction angle; Figure 2 In this context, 2θ represents the diffraction angle; Figure 5 In this context, "Intensity" refers to the intensity of the magnetic field, and "Magnetic field" refers to the magnetic field. Figure 6 In this context, Current density represents current density, and Potential represents electric potential. Figure 7 In this context, "overpotential" refers to an overpotential. Detailed Implementation

[0039] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only for explaining this application and are not intended to limit this application. All technologies implemented based on the above content of the present invention are included within the scope of protection intended by the present invention. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products or can be prepared by known methods.

[0040] In various embodiments of the specific implementation of the present invention, the Joule heating rapid heating device used consists of a gas path device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The device is model CIS-JH3.3-P, with an output voltage of 0-40V, an output current of 0-500A, a temperature measurement range of 0-3000°C, a power supply of 380V / 30A, and a current ramp-up time of 1ms.

[0041] In various embodiments of the specific implementation of the present invention, the ball mill used is model MH100, voltage is 200-240V, grinding container material is stainless steel, vibration frequency is 60-2400r / min / 40hz, grinding time is 1s-99min59s, and power is 400W. Example 1

[0042] (1) Mix 1 mol mannose, 1.75 mol lysine, 0.07 mol nickel nitrate, 0.35 mol cerium nitrate and 0.06 mol ytterbium nitrate, and place carbide grinding balls in a ball mill jar at a ball-to-material ratio of 15:1. Seal the ball mill jar and place it in a ball mill for ball milling. Set the ball mill speed to 1000 r / min and continuously ball mill for 1 hour in both forward and reverse directions to obtain the first precursor.

[0043] (2) Place 5g of the first precursor into the groove of the graphite sample stage of the Joule heating device, and then perform Joule heat treatment 4 times in air atmosphere. The Joule heat treatment temperature is 1000℃ and the heating rate is 2000℃ / s to obtain the second precursor.

[0044] (3) Prepare a mixed solvent by mixing 3 mL of water and 9 mL of acetone, then add 1 g of the second precursor to the mixed solvent, then ultrasonically clean twice for 0.4 h, and then dry at 80 °C for 8 h to obtain two-dimensional porous oxide nanosheets with compressive strain. Example 2

[0045] (1) Mix 1 mol mannose, 1.5 mol lysine, 0.05 mol nickel sulfate, 0.25 mol cerium nitrate and 0.05 mol ytterbium nitrate, and place carbide grinding balls in a ball mill jar at a ball-to-material ratio of 10:1. Seal the ball mill jar and place it in a ball mill for ball milling. Set the ball mill speed to 800 r / min and continuously ball mill for 1.5 h in both forward and reverse directions to obtain the first precursor.

[0046] (2) Place 5g of the first precursor above in the groove of the graphite sample stage of the Joule heating device, and then perform Joule heat treatment 3 times in air atmosphere. The Joule heat treatment temperature is 1600℃ and the heating rate is 1500℃ / s to obtain the second precursor.

[0047] (3) Prepare a mixed solvent by mixing 3 mL of water and 6 mL of acetonitrile, then add 1 g of the second precursor to the mixed solvent, then ultrasonically clean 3 times for 0.5 h, and then dry at 60 °C for 10 h to obtain two-dimensional porous oxide nanosheets with compressive strain. Example 3

[0048] (1) Mix 1 mol mannose, 2.0 mol lysine, 0.08 mol nickel acetate, 0.50 mol cerium nitrate and 0.08 mol ytterbium nitrate, and place carbide grinding balls in a ball mill jar at a ball-to-material ratio of 20:1. Seal the ball mill jar and place it in a ball mill for ball milling. Set the ball mill speed to 1500 r / min and continuously ball mill for 0.8 h in both forward and reverse directions to obtain the first precursor.

[0049] (2) Place 5g of the first precursor into the groove of the graphite sample stage of the Joule heating device, and then perform Joule heat treatment 5 times in air atmosphere. The Joule heat treatment temperature is 500℃ and the heating rate is 3000℃ / s to obtain the second precursor.

[0050] (3) Prepare a mixed solvent by mixing 3 mL of ethanol and 12 mL of acetonitrile, then add 1 g of the second precursor to the mixed solvent, then ultrasonically clean twice for 0.3 h, and then dry at 100 °C for 5 h to obtain two-dimensional porous oxide nanosheets with compressive strain. Example 4

[0051] (1) Mix 1 mol mannose, 1.70 mol lysine, 0.065 mol nickel nitrate, 0.32 mol cerium nitrate and 0.055 mol ytterbium nitrate, and place carbide grinding balls in a ball mill jar at a ball-to-material ratio of 15:1. Seal the ball mill jar and place it in a ball mill for ball milling. Set the ball mill speed to 1000 r / min and continuously ball mill for 1 hour in both forward and reverse directions to obtain the first precursor.

[0052] (2) Place 5g of the first precursor above in the groove of the graphite sample stage of the Joule heating device, and then perform Joule heat treatment 4 times in air atmosphere. The Joule heat treatment temperature is 900℃ and the heating rate is 2000℃ / s to obtain the second precursor.

[0053] (3) Prepare a mixed solvent by mixing 3 mL of ethanol and 8 mL of acetone, then add 1 g of the second precursor to the mixed solvent, then ultrasonically clean twice for 0.5 h, and then dry at 90 °C for 7 h to obtain two-dimensional porous oxide nanosheets with compressive strain. Comparative Example 1

[0054] The difference between Comparative Example 1 and Example 1 is that no ytterbium nitrate was added in step (1), while everything else remained the same. Comparative Example 2

[0055] The difference between Comparative Example 2 and Example 1 is that no nickel nitrate was added in step (1), while everything else remained the same. Comparative Example 3

[0056] The difference between Comparative Example 3 and Example 1 is that no nickel nitrate and ytterbium nitrate were added in step (1), while everything else remained the same. Comparative Example 4

[0057] The difference between Comparative Example 4 and Example 1 is that no mannose was added in step (1), while everything else remained the same. Comparative Example 5

[0058] The difference between Comparative Example 5 and Example 1 is that lysine was not added in step (1), while everything else remained the same. Comparative Example 6

[0059] The difference between Comparative Example 6 and Example 1 lies in the heating device used in step (2). The Joule heating rapid heating device is replaced with a high-temperature tube furnace, while the other steps remain unchanged. The specific operation is as follows:

[0060] 5g of the first precursor was placed in the center of the temperature zone of a high-temperature tube furnace and then calcined in air at a temperature of 1000℃ and a heating rate of 5℃ / min for 2 hours to obtain the second precursor. Comparative Example 7

[0061] The difference between Comparative Example 7 and Example 1 is that no proton solvent water was added in step (3), while the other steps remained unchanged. Comparative Example 8

[0062] The difference between Comparative Example 8 and Example 1 is that the nonprotic solvent acetone was not added in step (3), while the other steps remained unchanged. Comparative Example 9

[0063] The difference between Comparative Example 9 and Example 1 is that there is no ultrasound in step (3), while the other steps remain the same. Comparative Example 10

[0064] The difference between Comparative Example 10 and Example 1 lies in the grinding method in step (1): grinding with a ball mill is replaced with grinding with a mortar and pestle, while the other steps remain unchanged. The specific operation is as follows:

[0065] 1 mol of mannose, 1.75 mol of lysine, 0.07 mol of nickel nitrate, 0.35 mol of cerium nitrate, and 0.06 mol of ytterbium nitrate were mixed and placed in a mortar and ground for 1 hour to obtain the first precursor.

[0066] Application Example 1

[0067] Three mg of the compressive strain-bearing two-dimensional porous oxide nanosheet catalyst or commercial Pt / C prepared in the examples or comparative examples and 1 mg of commercial carbon black were added to an ethanol-Nafion mixed solution (0.48 mL of ethanol and 0.02 mL of 0.5% Nafion solution). After sonication for 3 h, a catalyst solution containing two-dimensional porous oxide nanosheets was obtained. 10 µL of the catalyst solution containing two-dimensional porous oxide nanosheets was pipetted onto a glassy carbon electrode and allowed to air dry to obtain a glassy carbon electrode modified with the two-dimensional porous oxide nanosheet catalyst. Electrochemical tests were performed on a CHI760E electrochemical workstation. Using the catalyst-modified glassy carbon electrode as the working electrode, a graphite rod as the counter electrode, saturated calomel as the reference electrode, and 0.1 M HClO4 aqueous solution as the electrolyte, linear sweep voltammetry (LSV) tests of the hydrogen evolution reaction were performed. The test results are shown in Table 1.

[0068] The two-dimensional porous oxide nanosheet catalysts with compressive strain obtained in Examples 1-4 and Comparative Examples 1-10 were subjected to nitrogen adsorption-desorption tests (N2-BET). The N2-BET tests included specific surface area tests and pore size distribution (NLDFT model full pore distribution) tests. The test results are shown in Table 1.

[0069]

[0070] Table 1 shows that comparing Examples 1-4 with Comparative Examples 1-3, doping with transition metals and rare earth elements helps generate lattice compressive strain and increases oxygen vacancy concentration. The doping effect of nickel is better than that of rare earth elements, while bimetallic doping has the best effect. Examples 1 and Comparative Examples 4-5 show that mannose and lysine are key factors in forming large pores and high specific surface areas; without their addition, in-situ chemical reactions cannot occur. Comparing Example 1 with Comparative Example 6 shows that the Joule heating device affects the specific surface area and pore size of the material, thus affecting the catalytic effect. The Joule heating device is a prerequisite for preparing materials with high pore size and high specific surface area. Examples 1 and Comparative Examples 7-8 show that protic and aprotic solvents not only remove impurities, organic residues, and unreacted substances but also affect the material's properties. Specific surface area is important, but the primary purpose is to remove impurities, organic residues, and unreacted substances, which affect the catalytic performance of the material. Cleaning with both protic and non-protic solvents improves the material's performance by approximately 41%. Examples 1 and 9 show that ultrasonic treatment not only helps remove impurities, organic residues, and unreacted substances but also optimizes the material's specific surface area, thus improving catalytic performance. Ultrasonic treatment improves the material's performance by approximately 57%. Examples 1 and 10 show that manual grinding has a significantly lower catalytic effect than ball milling. This is because ball milling produces smaller particles, which is more conducive to Joule heat treatment. Furthermore, the rapid grinding in ball milling generates heat, which helps pre-react the precursor materials and reduces the reaction conditions for Joule heat treatment. Therefore, ball milling of the reactants is another important factor in this preparation method.

[0071] Figure 1 The X-ray diffraction (XRD) patterns of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3 are shown. The XRD patterns of all samples correspond to the standard CeO2 (PDF#34-0394), indicating the successful synthesis of CeO2 porous nanosheets doped with different metals.

[0072] Figure 2 The figures show partially enlarged XRD patterns of the two-dimensional porous oxide nanosheets with compressive strain prepared in Examples 1 and Comparative Examples 1-3. As can be seen from the figures, compared with the catalysts obtained in Comparative Examples 1-3, the (111) diffraction peaks of Comparative Examples 1, 2, and 3 shifted to higher angles by approximately 0.34°, 0.27°, and 0.12°, respectively, confirming the CeO2 lattice compression caused by metal element doping. Importantly, the higher angle shift of the two-dimensional porous oxide nanosheet catalyst obtained in Example 1 indicates that Yb and Ni co-doping leads to more pronounced lattice compressive strain in the catalyst. The order of compressive strain is: Example 1 > Comparative Example 1 > Comparative Example 2 > Comparative Example 3.

[0073] Figure 3 The image shows a scanning electron microscope (SEM) image of the two-dimensional porous oxide nanosheet catalyst with compressive strain obtained in Example 1. As can be seen from the image, it is a two-dimensional nanosheet structure.

[0074] Figure 4 The figure shows the nitrogen adsorption-desorption (N2-BET) curve of the two-dimensional porous oxide nanosheet catalyst prepared in Example 1. As can be seen from the figure, the catalyst prepared in Example 1 exhibits a large H3-type hysteresis loop, indicating the presence of mesopores and macropores in the prepared sample.

[0075] Figure 5 EPR images of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3 are shown. The oxygen vacancy content was further determined by EPR, as shown below. Figure 5 As shown, both Example 1 and Comparative Examples 1-3 exhibit a symmetrical EPR signal peak at g=2.003, which is attributed to electrons on oxygen vacancies. The EPR signal intensity obtained by co-doping with Yb and Ni is stronger than that obtained by single doping with Yb and Ni or by no doping, indicating that the concentration order of oxygen vacancies on the catalysts of Example 1 and Comparative Examples 1-3 is: Example 1 > Comparative Example 1 > Comparative Example 2 > Comparative Example 3. This is consistent with... Figure 2 The XRD characterization results are consistent.

[0076] Figure 6 Linear sweep voltammetry (LSV) performance test results of the two-dimensional porous oxide nanosheet catalyst with compressive strain prepared in Example 1 for the hydrogen evolution reaction. Figure 6 As can be seen from the results in Table 1, compared with other samples, the electrode modified in Example 1 exhibits significantly enhanced HER activity, even outperforming the commercial Pt / C catalyst (45mV@10 mA•cm). -2This indicates that the catalyst has greater potential for industrial application. Meanwhile, the performance of CeO2 oxide nanosheets doped only with transition metals (Comparative Example 1), only with rare earth metals (Comparative Example 2), and without metal doping (Comparative Example 3), as well as two-dimensional porous oxide nanosheets prepared by traditional calcination methods (Comparative Example 6), is far inferior to the catalyst prepared by combining transition metals and rare earth elements as additives with a Joule heating device (Example 1). Therefore, dual doping with rare earth elements and transition metals more effectively enhances the HER performance of CeO2 than single metal doping or no doping. The fundamental reason for this difference is that rare earth elements and transition metal elements induce lattice compression strain within the catalyst during high-temperature doping, increasing the density of oxygen vacancy sites. This enhances the dissociation of water molecules at oxygen vacancy sites and improves hydrogen adsorption at adjacent oxygen vacancy sites. Furthermore, the Yb-O chemical bond formed by rare earth Yb doping is stronger than the Ce-O chemical bond, and Yb doping can stabilize oxygen vacancy sites, achieving excellent catalyst stability. Furthermore, the two-dimensional porous oxide nanosheets prepared by utilizing the rapid heating and cooling advantages of the Joule heating device assisted by the non-enzymatic browning reaction have the advantage of a large specific surface area, which can fully expose the abundant oxygen vacancy active sites, promote the electron transfer of CeO2 in HER, enhance the electron transport of oxides, and thus significantly enhance the electrocatalytic performance of HER.

[0077] Figure 7 The figures show the overpotential diagrams of the two-dimensional porous oxide nanosheets with compressive strain prepared in Example 1 and Comparative Examples 1-3. It can be seen from the figures that the catalyst prepared in Example 1 exhibits superior HER activity, requiring overpotentials of 28, 70, and 103 mV respectively to achieve 10, 100, and 200 mA cm⁻¹, respectively. -2 The current density was much lower than the overpotential required by the samples prepared in Comparative Examples 1-3 at the same current density, and Example 1 showed much higher activity than the comparative examples.

[0078] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of protection of the present invention.

Claims

1. A method for preparing two-dimensional porous oxide nanosheets with compressive strain, characterized in that, Includes the following steps: (1) After mixing mannose, lysine, nickel salt, cerium nitrate and ytterbium nitrate, solid-phase grinding was performed to obtain the first precursor; (2) The first precursor is subjected to Joule heat treatment in air atmosphere to obtain the second precursor; (3) The second precursor is added to a mixed solvent consisting of a protic solvent and a non-protic polar organic solvent, and after ultrasonic cleaning and vacuum drying, two-dimensional porous oxide nanosheets with compressive strain are obtained.

2. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (1), the nickel salt is nickel nitrate, nickel sulfate, or nickel acetate; the solid-phase grinding conditions are: ball weight percentage 10-20:1, ball mill speed 800-1500 r / min, and ball milling time 0.8-1.5 h.

3. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (1), the molar ratio of mannose, lysine, nickel salt, cerium nitrate, and ytterbium nitrate is 1:1.5-2.0:0.05-0.08:0.25-0.50:0.05-0.

08.

4. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (2), the conditions for Joule heat treatment are: heat treatment temperature 500-1600℃, heating rate 1500-3000℃ / s, and 3-5 Joule heat treatments.

5. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (3), the protic solvent is water or ethanol; the aprotic polar organic solvent is acetonitrile or acetone; the volume ratio of the protic solvent to the aprotic polar organic solvent in the mixed solvent is 1:2-4.

6. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (3), the ratio of the amount of the second precursor to the mixed solvent composed of proton solvent and non-proton polar organic solvent is 1g:9-15mL.

7. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (3), the ultrasonic cleaning conditions are: ultrasonic cleaning time 0.3-0.5h, ultrasonic cleaning 2-3 times.

8. The method for preparing two-dimensional porous oxide nanosheets with compressive strain according to claim 1, characterized in that, In step (3), the vacuum drying conditions are: drying time 5-10h, drying temperature 60-100℃.

9. An application of a two-dimensional porous oxide nanosheet with compressive strain prepared by the preparation method according to any one of claims 1-8, characterized in that, It was used as an electrochemical catalyst in the hydrogen evolution reaction under alkaline electrolyte conditions.

Citation Information

Patent Citations

  • Method for preparing Ru-based oxide catalyst doped with metal atoms on surface by ion exchange method and application of Ru-based oxide catalyst

    CN116288495A

  • Trivalent rare earth doped cerium dioxide supported metal catalyst as well as preparation method and application thereof

    CN116966911A

  • Thin-layer two-dimensional oxide material and preparation and application thereof

    CN117448793A

  • Porous metal oxide nanosheet, preparation method and application thereof

    CN111348676A

  • Preparation method of two-dimensional non-layered metal oxide porous nanosheet

    CN114702011A